2023
DOI: 10.3389/ti.2023.11564
|View full text |Cite
|
Sign up to set email alerts
|

European Society of Organ Transplantation (ESOT) Consensus Statement on Prehabilitation for Solid Organ Transplantation Candidates

Coby Annema,
Stefan De Smet,
Ellen M. Castle
et al.

Abstract: There is increasingly growing evidence and awareness that prehabilitation in waitlisted solid organ transplant candidates may benefit clinical transplant outcomes and improve the patient’s overall health and quality of life. Lifestyle changes, consisting of physical training, dietary management, and psychosocial interventions, aim to optimize the patient’s physical and mental health before undergoing surgery, so as to enhance their ability to overcome procedure-associated stress, reduce complications, and acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Exercise is defined as a subset of physical activity that is planned, structured and repetitive and has an objective of the improvement or maintenance of physical fitness 31. Multimodal and multicomponent interventions in this population are clinically important due to the need to address the complex interaction between the physical and psychological health of the patient prior to transplantation 22…”
Section: Methods and Analysismentioning
confidence: 99%
“…Exercise is defined as a subset of physical activity that is planned, structured and repetitive and has an objective of the improvement or maintenance of physical fitness 31. Multimodal and multicomponent interventions in this population are clinically important due to the need to address the complex interaction between the physical and psychological health of the patient prior to transplantation 22…”
Section: Methods and Analysismentioning
confidence: 99%
“…These initial studies indicated that (i) exercise-based prehabilitation is safe, (ii) kidney transplant candidates consider exercise-based prehabilitation appropriate, acceptable, satisfying, and effective to improve physical function, and (iii) exercise-based prehabilitation improves physical function, cardiorespiratory fitness, muscle strength, physical activity levels, fatigue, frailty, body composition, and postoperative length of stay [28–31]. Recently, a consensus meeting on prehabilitation for solid organ transplant candidates was held under the flag of the European Society of Organ Transplantation (ESOT) [32 ▪ ]. Recommendations from this meeting stated that given the limited body of literature evidence, high-quality studies on prehabilitation in solid organ transplant candidates are needed, in which both the effectiveness and implementation of pretransplant multimodal prehabilitation are addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Recommendations from this meeting stated that given the limited body of literature evidence, high-quality studies on prehabilitation in solid organ transplant candidates are needed, in which both the effectiveness and implementation of pretransplant multimodal prehabilitation are addressed. In addition, it was recommended that a Core Outcome Set and preferred assessment methodology should be developed to enable adequate comparison of the study results and identify the optimal modality, timing, duration, and delivery characteristics of prehabilitation interventions [32 ▪ ]. At the moment, two RCT's on multimodal prehabilitation interventions in people living with CKD who are also waitlisted for transplantation are underway: the FRAIL-MAR-study (NCT04701398) [33] and the PreCareTx-study (NCT05489432) [34].…”
Section: Introductionmentioning
confidence: 99%
“…1 Prehabilitation is now gradually considered to be an essential part of the enhanced recovery pathway for those receiving kidney transplantation. 2 A recently published multi-center clinical trial from the UK by Greenwood and colleagues 3 concluded positive findings on evaluating the effects of a digital health intervention (Kidney BEAM) to enhance physical activity in people with CKD including transplant waitlist patients. In particular, the Kidney BEAM physical activity platform demonstrated to significantly improve mental health-related quality of life in patients with CKD.…”
mentioning
confidence: 99%
“…1 Prehabilitation is now gradually considered to be an essential part of the enhanced recovery pathway for those receiving kidney transplantation. 2…”
mentioning
confidence: 99%